1984
DOI: 10.1038/bjc.1984.236
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive use and malignant melanoma in Australia

Abstract: (Beral et al., 1977;Adam et al., 1981;Bain et al., 1982;Holly et al., 1983), although the increase was not always statistically significant. We report here the findings of a case control study carried out in New South Wales, Australia, designed to examine these relationships. MethodsThe study design has been described elsewhere (Beral et al., 1982

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1
2

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 7 publications
5
53
1
2
Order By: Relevance
“…But, neither of these studies specifically examined current vs past use of oral contraceptives. Another case -control study restricted to women less than 55 years of age found an elevated risk (OR=1.5; 95% CI=1.0 -2.1) in relation to 5 or more years of oral contraceptive use, among those who began use 10 or more years before (Beral et al, 1984). While this study met the eligibility criteria for our analysis, the original data were no longer available.…”
Section: Epidemiologymentioning
confidence: 92%
See 3 more Smart Citations
“…But, neither of these studies specifically examined current vs past use of oral contraceptives. Another case -control study restricted to women less than 55 years of age found an elevated risk (OR=1.5; 95% CI=1.0 -2.1) in relation to 5 or more years of oral contraceptive use, among those who began use 10 or more years before (Beral et al, 1984). While this study met the eligibility criteria for our analysis, the original data were no longer available.…”
Section: Epidemiologymentioning
confidence: 92%
“…Eleven case -control studies met the analysis criteria (Beral et al, 1984;Holman et al, 1984;Gallagher et al, 1985;Green and Bain, 1985;Østerlind et al, 1988;Swerdlow et al, 1986;Elwood et al, 1990;Zanetti et al, 1990;Kirkpatrick et al, 1994;Langholz et al, 2000) and data were available for all but one of these (Beral et al, 1984). The investigators from all of the remaining studies agreed to take part.…”
Section: Selection Of Studies For Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Failure to find an association between melanoma and oral contraceptive use may be due to the broad categorization of 'ever users'. A few studies have reported modest elevations in melanoma risk among women with longer durations of use or with longer times since first use (Bain et al, 1982;Holly et al, 1983;Beral et al, 1984;Le et al, 1992). However, previous research has been limited by the predominance of case-control designs that rely on recall of oral contraceptive use.…”
mentioning
confidence: 99%